Can we study the family environment through census data? A comparison of households, dwellings, and domestic units in rural Mali. (2nd January 2020) - Hertrich, Véronique; Feuillet, Pascaline; Samuel, Olivia; Doumbia Gakou, Assa; Dasré, Aurélien
Abstract : Are 'statistical households', as defined in national censuses, able to describe the family environment in Africa? Do they correspond to the family units that individuals identify with? To address this issue, we build on a follow-up survey in south-east Mali, which links national censuses with local censuses at the individual level (N ≈ 28, 000 census observations). Three cross-sectional snapshots of family arrangements are compared: households recorded in national censuses, and family economic units and residential units recorded by local censuses. The national census household data appear poorly suited to documenting family living arrangements. They do not account for family economic units or residential units, but are highly conditioned by a normative representation centred on the nuclear family. Therefore, they fail to describe the complexity and diversity of people's living spaces, making particular types of living arrangements invisible and increasing the likelihood of omitting individuals who do not fit into a nuclear model.